ILUSI KOMPETENSI DALAM PENGGUNAAN AI CODING ASSISTANT: INTERPRETASI DESKRIPTIF KETERGANTUNGAN KOGNITIF MAHASISWA INFORMATIKA DALAM PENYELESAIAN TUGAS PEMROGRAMAN - Lie, Eiffeilin Gracia Mario; Lim, Caronwin; Pakpahan, Ikhwan El Akmal (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The use of AI Coding Assistant in completing programming assignments is becoming increasingly common among informatics students. This technology provides convenience and efficiency, but excessive use has the potential to create an illusion of competence and cognitive dependence. This study aims to describe the level of illusion of competence and cognitive dependence of informatics students in completing programming assignments using AI Coding Assistant. This study uses a descriptive quantitative approach with an instrument, namely a questionnaire distributed to third-semester informatics students at Satya Terra Bhinneka University. Existing data will be analyzed using descriptive statistics to describe the pattern of AI use, perception of self-competence, and the level of cognitive dependence of students. The results of this study are expected to provide an understanding of the impact of AI Coding Assistant on learning programming courses and become a basis for using them in a balanced manner in learning. Keyword: Illusion of Competence, AI Coding Assistant, Cognitive Dependency, Informatics Students, Programming Assignments Abstrak: Kehadiran AI Coding Assistant dalam penyelesaian tugas pemrograman semakin umum di kalangan mahasiswa informatika. Teknologi ini memberikan kemudahan serta efisiensi, namun penggunaan yang berlebihan memiliki potensi untuk menimbulkan ilusi kompetensi dan ketergantungan kognitif. Penelitian ini bertujuan untuk mendeskripsikan tingkat ilusi kompetensi dan ketergantungan kognitif mahasiswa informatika dalam penyelesaian tugas pemrograman menggunakan AI Coding Assistant. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan instrumen yaitu kuesioner yang disebarkan kepada mahasiswa informatika semester 3 Universitas Satya Terra Bhinneka. Data yang sudah ada akan dianalisis secara statistik deskriptif untuk menggambarkan pola penggunaan AI, persepsi kompetensi diri, serta tingkat ketergantungan kognitif mahasiswa. Hasil penelitian diharapkan bisa memberikan pemahaman mengenai dampak AI Coding Assistant terhadap pembelajaran mata kuliah pemrograman dan menjadi suatu dasar untuk menggunakannya secara seimbang dalam pembelajaran. Kata kunci: Ilusi Kompetensi, AI Coding Assistant, Ketergantungan Kognitif, Mahasiswa Informatika, Tugas Pemrograman